1998
DOI: 10.1016/s0079-1946(98)00139-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between magnetic parameters and chemical composition of lake sediments from northern Bohemia—Preliminary study

Abstract: Abstract.Recently, magnetic measurements have been used m outline areas with increased loading of toxic metals due to industrial activity. It is supposed that magnetic minerals, which are easily detectable, can cant toxic metals of anthropic origin. However, physical background of this relationship is not comprehended yet. In this study, we present our first results on statistical correlation of various magnetic parameters on one side and chemical composition on the other, obtained on sediments from the bottom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…Arkell et al, 1983;Oldfield et al, 1985White et al, 1997;Walden et al, 1995Walden et al, , 1997Schmidt et al, 1999;Wheeler et al, 1999). Many of the studies have explored the relationship between mineral magnetic measurements and chemical/physical properties of sediments and soils (Oldfield et al, 1985;Oldfield and Yu, 1994;Clifton et al, 1997Clifton et al, , 1999Chan et al, 1998;Petrovsky et al, 1998;Xie et al, 1999Xie et al, , 2000Booth, 2002). Based on these investigations, mineral magnetic measurements have been identified as a suitable tool for determining sediment provenance (Oldfield and Yu, 1994;Booth, 2002), sediment transport pathways (Lepland and Stevens, 1996), and also to serve as a proxy for geochemical, radioactivity, organic matter content and particle size data (Bonnett et al, 1988;Oldfield et al, 1993;Hutchinson and Prandle, 1994;Clifton et al, 1997Clifton et al, , 1999Xie et al, 1999Xie et al, , 2000Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Arkell et al, 1983;Oldfield et al, 1985White et al, 1997;Walden et al, 1995Walden et al, , 1997Schmidt et al, 1999;Wheeler et al, 1999). Many of the studies have explored the relationship between mineral magnetic measurements and chemical/physical properties of sediments and soils (Oldfield et al, 1985;Oldfield and Yu, 1994;Clifton et al, 1997Clifton et al, , 1999Chan et al, 1998;Petrovsky et al, 1998;Xie et al, 1999Xie et al, , 2000Booth, 2002). Based on these investigations, mineral magnetic measurements have been identified as a suitable tool for determining sediment provenance (Oldfield and Yu, 1994;Booth, 2002), sediment transport pathways (Lepland and Stevens, 1996), and also to serve as a proxy for geochemical, radioactivity, organic matter content and particle size data (Bonnett et al, 1988;Oldfield et al, 1993;Hutchinson and Prandle, 1994;Clifton et al, 1997Clifton et al, , 1999Xie et al, 1999Xie et al, , 2000Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years magnetic measurements, which are simple, rapid, inexpensive, and nondestructive, are increasingly being used in a wide range of environmental sciences such as identification of source of industrial pollutants and atmospheric particulates (Hunt et al, 1984;Kapicka et al, 2003;Lecoanet et al, 2003;Moreno et al, 2003;Shu et al, 2001), mapping of soils and sediments pollution (Hanesch et al, 2003;Hoffmann et al, 1999;Matzka and Maher, 1999), and a proxy parameter for quantifying contents of heavy metals in certain environments (Chan et al, 2001;Petrovsky et al, 1998;2000). Many works on soils, sediments and atmospheric dusts have shown that the magnetic properties of airborne particles, industrially polluted soils and sediments were strongly associated with heavy metal concentration and mutagenic organic compounds (Hunt et al, 1984;Lecoanet et al, 2003;Morris et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For obvious reasons magnetic methods can be used for the characterisation of pollution and have become commonplace by many international laboratories (e.g. Dearing et al, 1996;Petrovsky et al, 1998;Evans & Heller, 2003;Hanesch et al, 2003).…”
Section: Basic Principlesmentioning
confidence: 99%